(3faKGJ GdeUOhQ aj JPcQ TehS GdOjf hGdHOhQ (B((3OjhGf(B)s - (3eMeO Hf eMeO Hf eMeO Hf CejQ MGL GHf GdeDbJ ,GHf GejQ MGL , TeS GdOjf CHh YHO Gddg,J (B879 (3g` s ((3bUHI GdMSjf s)
(3ChdgG (B:s
(3Chd GdehLhO efgG CKfGA (B"(3GdfaKI GdKGfjI YTQI(B" (3bhdg(B: (3hMGda GdMRf ajgG eG GSJWYJ hdG JCda SQhQkG hNGda cd Pj WQH s
(3BNQgG (B:s
(3Ke GMYdfj aLhI JMcj GdLOGhd eG Hjf GdSWhQ hbQeW CMQa Gdcde hbO hbY GdaQGZ ef cJGHI gPG GdOjhGf s
(3GdNW ajg HYV GdVHWs
(3hHHYV ChQGbgG JbWjY JdjgG SJ hQbGJ aj QKGA GdMSjf hgh GdehVhY faSgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B49 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B274 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B208s
Keywords: (3GdCOHs